Design of the effect of adaptive servo‐ventilation on survival and cardiovascular hospital admissions in patients with heart failure and sleep apnoea: the ADVENT‐HF trial. (April 2017) - Lyons, Owen D.; Floras, John S.; Logan, Alexander G.; Beanlands, Robert; Cantolla, Joaquin Durán; Fitzpatrick, Michael; Fleetham, John; John Kimoff, R.; Leung, Richard S.T.; Lorenzi Filho, Geraldo; Mayer, Pierre; Mielniczuk, Lisa; et al.
Abstract : Introduction: Both types of sleep‐disordered breathing (SDB), obstructive and central sleep apnoea (OSA and CSA, respectively), are common in patients with heart failure and reduced ejection fraction (HFrEF). In such patients, SDB is associated with increased cardiovascular morbidity and mortality but it remains uncertain whether treating SDB by adaptive servo‐ventilation (ASV) in such patients reduces morbidity and mortality. Aim: ADVENT‐HF is designed to assess the effects of treating SDB with ASV on morbidity and mortality in patients with HFrEF. Methods: ADVENT‐HF is a multicentre, multinational, randomized, parallel‐group, open‐label trial with blinded assessment of endpoints of standard medical therapy for HFrEF alone vs. with the addition of ASV in patients with HFrEF and SDB. Patients with a history of HFrEF undergo echocardiography and polysomnography. Those with a left ventricular ejection fraction ≤45% and SDB (apnoea–hypopnoea index ≥15) are eligible. SDB is stratified into OSA with ≥50% of events obstructive or CSA with >50% of events central. Those with OSA must not have excessive daytime sleepiness (Epworth score of ≤10). Patients are then randomized to receive or not receive ASV. The primary outcome is the composite of all‐cause mortality, cardiovascular hospital admissions, new‐onset atrial fibrillation requiring anti‐coagulation but not hospitalization, and delivery of an appropriate discharge from an implantable cardioverter‐defibrillator not resulting in hospitalization during a maximum follow‐up time of 5 years. Conclusion: The ADVENT‐HF trial will help to determine whether treating SDB by ASV in patients with HFrEF improves morbidity and mortality.